Pelaksanaan 'Amaliyah Tadr S (Praktek PengalamanLapangan) Di Pondok Pesantren Ta'mirul IslamSurakarta Pada Semester Genap Tahun Pelajaran2015/2016 - Khofiya, Riqqoh, Drs. Saifuddin Zuhri, M.Ag (2017)
Many of the new teachers are poorly trained and do not have much experience in teaching so it needs a lot of adjustments in the beginning of teaching. And so it causes students being less than optimal in receiving lesson. In terms of that, the prospective teachers are required to keep practicing and seeking as much as possible experience in teaching practice in order to be able to cope with the problems that arise when they are in class later. This study discusses: implementation of ʻamaliyah a r s (Practice of Field Experience) in Surakarta Ta'mirul Islam boarding school in the second semester of the academic year 2015/2016? This study aimed to describe the implementation of ʻamaliyah a r s (Practice of Field Experience) in Surakarta Ta'mirul Islam boarding school in the second semester of the academic year 2015/2016. This research is a field research intended to collect data and information on the facts that occurred. Collecting data has used interviews, observation and documentation, while the data analysis has used a qualitative description. Based on the results of research the implementation of ʻamaliyah a r s at Surakarta Ta'mirul Islam boarding school in the second semester of the academic year 2015/2016 is as follows: (1) Implementation of ʻamaliyah a r s at Surakarta Ta'mirul Islam Boarding School in second semester performed by sixth grade students of KMI is a graduation requirement; (2) ʻAmaliyah a r s in this study is conducted in the second semester of the academic year 2016/2017 program; (3) the implementation of ʻamaliyah a r s carried out on a scheduled basis, starting with ʻamaliyah a r s done by one of the students who is watched by most of the cleric and all friends of sixth grade students. Further more, it will be done in groups with two musyrifs (supervisor) in each execution of ʻamaliyah a r s; (4) Implementation of ʻamaliyah a r s at Surakarta Ta'mirul Islam boarding school in the second semester of the academic year 2015/2016 has done well and effectively because each students has been able to demonstrate the skills taught in the real class. The strengthen of implementation of ʻamaliyah a r s in Surakarta Ta'mirul Islam boarding school among others: (1) Providing teaching skills for students at Surakarta Ta'mirul Islam boarding school; (2) Motivating students to become professional teachers, improving the skills of students in making preparation for teaching; (4) Improving teaching skills of students in a real class. As the shortage of implementation of ʻamaliyah a r s (Practice of Field Experience) at Surakarta Ta'mirul Islam boarding school includes: (1) Being lack of facilities in the use of instructional media; (2) Learning micro teaching; (3) Teaching practices with colleagues have not practiced before the ʻamaliyah a r s in the classroom in real time; (4) Method used in the implementation of ʻamaliyah a r s is less varied.